Ageing Knowledge Structure in Global River Basins - Wei, Yongping; Wu, Shuanglei; Lu, Zhixiang; Wang, Xuemei; Wu, Xutong; Xu, Li; Sivapalan, Murugesu (Frontiers in Environmental Science, 2022)
Understanding the historical evolution of science development for rethinking science in the Anthropocene is crucial for our future survival. This paper analyzed the knowledge development of the top 95 most researched river basins in the Web of Science database in the past three decades (1987-2017) using a network metric-based framework, comprising one scalar metric and three structural metrics: equality, efficiency, and resilience. We found that the highly researched river basins accounting about 30% of total publications, including the Yangtze River and the Great Lakes, demonstrated the “ageing” knowledge structures characterized by high inequality, low efficiency, and large redundancy with continuous expansion in scales. Dominations of knowledge interactions among Environmental Sciences, Water Resources, Marine Science and Freshwater Biology contributed to this knowledge structure. Transformations of both the composition and structure of the knowledge system is required to support global river basin management in the Anthropocene.